THE UNEXPECTED NEGATIVE IMPACT OF SERVICE QUALITY ON RETAIL PERFORMANCE IN TRADITIONAL BUILDING STORES: EVIDENCE FROM ASBESTOS-CONTAINING PRODUCTS IN SURABAYA RAYA - Dendy Tirtoadisuryo (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to analyze the unexpected negative impact of service quality on retail performance in the sale of asbestos-based products in traditional building stores in Greater Surabaya. The research method used was quantitative with a cross-sectional design and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, involving 120 building stores that met purposive sampling criteria. The results showed that service quality had a significant negative effect on marketing performance (β = –0.259; p < 0.01) and indirectly reduced sales performance through the mediation of marketing performance (β = –0.087; p < 0.01). The findings also indicated that asbestos knowledge reinforced the negative effect of service quality on marketing performance (β = –0.214; p < 0.01), indicating that consultative services actually increase perceived health risks, decrease trust, and weaken purchase intentions. In conclusion, service quality in the context of high-risk products like asbestos can be a strategic liability, not an asset, and therefore, service strategies need to be directed at educating consumers about safer product alternatives.